DIVERSITY OF MEDICINAL PLANT RESOURCES USED IN SOME ETHNIC MINORITY COMMUNITIES IN YEN NINH COMMUNE, PHU LUONG DISTRICT, THAI NGUYEN PROVINCE - Thi Thu Hien, Nguyen; Van Hung, Duong; Hai Hoa, Nguyen; Hoang Vuong, Dang (Journal of Forestry Science and Technology, 2018)
This research was conducted to assess the diversity of medicinal plant resources in Yen Ninh commune, Phu Luong district, Thai Nguyen province. The results of research have identified initially 149 species of medicinal plants in 137 genera and 74 families, which the ethnic minority communities have used for diseases prevention and treatment. There are five main life forms of the medicinal plants, including herbaceous (53.02%), vines (19.46%), small wood trees (14.09%), shrubs (6.71%) and moderate wood trees (6.71%). These medicinal plants were found in many types of habitats, including forests, gardens, hills and streams. Regarding plant materials used as medicine, leaves, roots and whole plants are common used components. The results show that there are 22 groups of diseases which could be cured by the experience of using medicinal plants of some ethnic minority communities in the study area, of which 7 groups of diseases occupy the highest rate including weather sickness, osteoarthritis, stomach disease, respiratory diseases, skin diseases, wound diseases, heat. There are six endangered medicinal plants in Yen Ninh commune, Phu Luong district, including: Nervilia fordii Schultze, Fibraurea tinctoria Lour, Cycas revoluta Thunb, Rauvolfia verticillata (Lour.) Baill., Tinospora capillipes Gagnep, Ardisia silvestris Pit.